2014
DOI: 10.1099/mic.0.078840-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of agronomically relevant fungal phytopathogens by tyrocidines, cyclic antimicrobial peptides isolated from Bacillus aneurinolyticus

Abstract: The tyrocidines, a complex of analogous cyclic decapeptides produced by Bacillus aneurinolyticus, exhibited noteworthy activity against a range of phytopathogenic fungi, including Fusarium verticillioides, Fusarium solani and Botrytis cinerea. The activity of the tyrocidine peptide complex (Trc mixture) and purified tyrocidines exhibited minimum inhibition concentrations below 13 mg ml "1 (~10 mM) and was significantly more potent than that of the commercial imidazole fungicide, bifonazole. Although the tyroci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 75 publications
0
35
0
Order By: Relevance
“…There is a possibility that the antifungal action of the tyrocidines may not only be the result of membranolytic activity, particularly as fungal spores treated with tyrocidines tended to form non-viable hyperbranched structures, which eludes to an alternative target or mode of action [5]. The major tyrocidines have good activity against the planktonic form of pathogenic yeast C. albicans, as well as activity to prevent its biofilms [5]. This study also indicated that membrane leakage is part of the tyrocidine mode of anti-candida action.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…There is a possibility that the antifungal action of the tyrocidines may not only be the result of membranolytic activity, particularly as fungal spores treated with tyrocidines tended to form non-viable hyperbranched structures, which eludes to an alternative target or mode of action [5]. The major tyrocidines have good activity against the planktonic form of pathogenic yeast C. albicans, as well as activity to prevent its biofilms [5]. This study also indicated that membrane leakage is part of the tyrocidine mode of anti-candida action.…”
Section: Introductionmentioning
confidence: 97%
“…Lytic activity has been observed for the tyrocidines against Gram-positive bacteria [3], but not against P. falciparum and it was proposed that the tyrocidines interfere with parasite development [6]. A natural extract from tyrothricin, the tyrocidine mixture (Trc mixture) containing the six major tyrocidines, has significant antifungal activity against a broad array of filamentous fungi, many of which are plant pathogens, but also a number of human pathogens [5]. Fluorescent microscopy of fungal hyphae treated with the tyrocidines alluded to the likelihood that antifungal activity leads to membrane leakage [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations